Development of Peramal Board Media Based on Bruner’s Theory in Addition and Subtraction of Decimal for Grade IV Primary School - Adaninggar Prameswari; Nursiwi Nugraheni (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: Learning media is essential for creating interactive and fun lessons. However, conventional methods are still dominant in practice. An interview with the fourth-grade form teacher revealed that limited use of learning media in mathematics leads to monotonous lessons, affecting students’ focus and ability to solve math story problems. This study aimed to (1) develop media design, (2) test media feasibility, and (3) test the effectiveness of the Peramal Board media based on Bruner's theory to improve grade IV student’s ability to solve math story problems. This study is based on the ADDIE model with a mixed-method research approach. The results showed that the feasibility of the Peramal Board from a material expert was 91.67%, media expert 95%, student response 100%, and teacher response 93.33%, with the category very feasible. The effectiveness of the Peramal Board is indicated by an improvement in learning outcomes of 3.986 with a sig. (tailed-2) value of 0.000. The N-Gain test result of 0.7720 > 0.7 shows a high criterion. The result of this study is that Peramal Board has successfully improved the ability of fourth-grade students to solve decimal addition and subtraction story problems. Abstrak: Media pembelajaran sangat penting untuk menciptakan pembelajaran yang interaktif dan menyenangkan. Namun, metode konvensional masih dominan dalam praktik. Wawancara dengan wali kelas IV mengungkapkan bahwa keterbatasan penggunaan media pembelajaran dalam matematika menyebabkan pembelajaran menjadi monoton, yang memengaruhi fokus siswa dan kemampuan mereka dalam menyelesaikan soal cerita matematika. Penelitian ini bertujuan untuk (1) mengembangkan desain media, (2) menguji kelayakan media, dan (3) menguji efektivitas media Papan Peramal berdasarkan teori Bruner untuk meningkatkan kemampuan siswa kelas IV dalam menyelesaikan soal cerita matematika. Penelitian ini didasarkan pada model ADDIE dengan pendekatan penelitian metode campuran. Hasil penelitian menunjukkan bahwa kelayakan Papan Peramal dari ahli materi sebesar 91,67%, ahli media 95%, respon siswa 100%, dan respon guru 93,33%, dengan kategori sangat layak. Efektivitas Papan Peramal ditunjukkan dengan peningkatan hasil belajar sebesar 3,986 dengan nilai sig. (2-tailed) sebesar 0,000. Hasil uji N-Gain sebesar 0,7720 > 0,7 menunjukkan kriteria tinggi. Hasil penelitian ini adalah bahwa Papan Peramal berhasil meningkatkan kemampuan siswa kelas IV SD dalam menyelesaikan soal cerita penjumlahan dan pengurangan desimal.